DEVELOPMENT OF A HIGH BCAA (BRANCHED-CHAIN AMINO ACIDS) ENTERAL FORMULA BASED ON TEMPE FLOUR (Rhizopus Oryzae) AND WHEY PROTEIN ISOLATE FOR PATIENTS WITH LIVER CIRRHOSIS - Prativi, Afina; Saleky, Yohannes Wilihelm; Suparman, Suparman; Hapsari, Agustina Indri; Mulyo, Gurid; Agung, Fred (Jurnal Gizi dan Dietetik, 2025)
Liver cirrhosis is the main cause of morbidity and mortality in chronic liver disease in the world. Conditions that occur in liver cirrhosis include decreased liver function, malnutrition due to inadequate oral intake and impaired absorption which is exacerbated by hypermetabolism and hepatic encephalopathy due to ammonia accumulation, causing a decrease in blood plasma BCAAs. Providing BCAA supplementation provides positive results in patients with liver cirrhosis. This study developed an innovative high-BCAA enteral formula based on tempeh flour and whey protein isolate (Hepatolate).The aim of this study was to evaluate organoleptic properties, nutrient and BCAA content of this product. The research design was experimental, utilizing a completely randomized design with three treatments, conducted at the RSUP Dr. Hasan Sadikin Bandung. The organoleptic properties were tested by 20 semi-trained panelists, and proximate analysis was performed at the Saraswanti Indo Genetech in Padang. The results indicated no significant differences in the organoleptic quality regarding color (p=0.610), aroma (p=0.400), taste (p=0.384), and texture (p=0.067. The best formula being third formulation. Serving size The optimal of Hepatolate is 250 ml, containing 214.42 kcal, 12.05 grams of protein, 4.39 grams of fat, 21.70 grams of carbohydrates, and 3.69 grams of BCAA. The selling price for the best Hepatolate product per serving is IDR 8.899,-. Future research is recommended to assess consumer acceptability, shelf life, and further improvements in the formulation, particularly regarding carbohydrate content.